Inscription parameters in bulk polymer - Ioannou, Andreas; Kalli, Kyriacos; Yerolatsitis, Stephanos (My University, 2025)
The research explores critical laser parameters—including pulse energy and repetition rate, -and their influence on the polymer's refractive index modification, structural integrity, and optical performance. The plane-by-plane FSL inscription technique is employed to achieve high spatial resolution and controlled material modifications. Various polymers, such as PMMA (Polymethyl-methacrylate), PC (Polycarbonate), PSU (Polysulfone), FEP (Fluorinated-Ethylene-Propylene), were selected for their suitability in biomedical and specifically for implantation in the brain and spinal cord within the Move2Treat's context.
Keywords: femtosecond laser; Polymer optical fibres